The preferences of MOOD realized in Folklore album by Taylor Swift - Kamaliah, Adistia Mursyidatul; Masrokhin, Masrokhin; Amri, M. Misbahul; Laksmi, Ekaning Dewanti (citeus, 2024)
Interpersonal meaning expresses the social role connections that exist between both parties in communication. The current study aimed at discovering interpersonal mean-ing in related to MOOD preferences from inside of Folklore album arranged by Taylor Swift. MOOD refers to the grammatical structure that indicates the function of a sen-tence in expressing the songwriter’s attitude. Using a qualitative research method, this paper reports on MOOD choices as well as speech functions from inside of the chosen tunes of Folklore album. This research revealed that MOOD type of declarative clause and speech function of statement dominate the lyrics of the chosen tunes, while speech function of offer does not appear. Thus, the songwriter transmits the thoughts on the lyrics to the audience by providing the information. Considering the supplied criteria, the use of the singular pronoun “I” as the primary subject effectively fosters a sense of interpersonal connections. However, a deeper investigation of interpersonal meaning is required in order to enhance students’ English skills, particularly in the expression of attitudes in various language capabilities in related to reading, listening, as well as speaking.